Use of mycorrhiza in organic farming. Issue 1 (June 2021) - Tawaha, A R M; Khanum, S; Imran; Amanullah; Al Tawaha, A R; Thangadurai, D; Sangeetha, J; Rauf, A; Khalid, S; Saranraj, P; Safari, Z S; Zahid, N A; et al.
Abstract: In this review we discussed the role of mycorrhiza in organic farming. How mycorrhizal association, will help to improve and encouraging the idea of organic farming. How mycorrhizal association help the plants to grow and yield better without applying of chemical fertilizers and following the conventional farming practices. We discussed how AMF help plant to uptake nutrients, releasing chemicals which help plants to grow proper, developing resistance against weeds, pest and other microbes.